'Linguartistics'. (1st September 2018) - Minden, Laure Van
An attempt to define my artistic practice would be fine art calligraphy or lettering art. Drawing with words or writing drawings has become a way of explaining my research. In fact, text IS my practice and the dialogue between text and image is very real: the text is image and the image is created out of text. One does not exist without the other: they form an entity that develops a connection with myself and ultimately the viewer. Art as Text as Art is the venture of 'linguartistics'.